AUSTRALIA-INDONESIA COUNTER-TERRORISM COOPERATION - Adhi Cahya Fahadayna (Jurnal Transformasi Global, 2018)
Bali bombing 2002 is a tragic phenomenon for both countries, Australia and Indonesia. Bali bombing killed 202 peoples, which are 88 Australian and 33 Indonesian. This event becomes a critical phase for the Australia-Indonesia security cooperation after the East Timor incident in 1999. Australia initiates several programs to support Indonesian counter-terrorism effort. Indonesia also faces a challenge after m 1999. The Indonesian police –as the main body of law enforcement– do not have any experience in combatting terrorism. Australia facilitates the USA –as principal actors of global counter-terrorism– to support Indonesia's counter-terrorism policy. Australia and Indonesia have reached formal security cooperation with the ratification of Lombok treaty. This paper will examine Australia-Indonesia security cooperation in the respond to a terrorist threat using Islamic radicalization theory and regional security complex theory.